Six months into the war: a first-wave study of stress, anxiety, and depression among in Ukraine - Kurapov, Anton; Danyliuk, Ivan; Loboda, Andrii; Kalaitzaki, Argyroula; Kowatsch, Tobias; Klimash, Tamara; Predko, Viktoriia (Frontiers in Psychiatry, 2023)
Objective: This study examines the prevalence and predictors of mental health issues, specifically anxiety, depression, and stress, among Ukrainians in the ongoing military conflict with Russia. Method: A cross-sectional correlational study was conducted six months after the beginning of the conflict. Sociodemographic factors, traumatic experiences, anxiety, depression, and stress were assessed using various measures. The study included 706 participants, both men and women, from different age groups and living in various regions of Ukraine. Results: The study found that a large portion of the Ukrainian population shows increased levels of anxiety, depression, and stress due to the war. Women were found to be more vulnerable to mental health issues than men, and younger people were found to be more resilient. Worsened financial and employment statuses predicted increased anxiety. Ukrainians who fled the conflict to other countries exhibited higher levels of anxiety, depression, and stress. Direct exposure to trauma predicted increased anxiety and depression, while war-related exposure to "other stressful events" predicted increased acute stress levels. Conclusions: The findings of this study highlight the importance of addressing the mental health needs of Ukrainians affected by the ongoing conflict. Interventions and support should be tailored to address the specific needs of different groups, particularly women, younger individuals, and those with worsened financial and employment statuses.